Using songs for teaching 21st century learners - Yee, Isabel Pin Tsin * (Sunway College Kuala Lumpur, 2015)
Recent studies have shown that songs may enhance learning as they function as mnemonic devices to increase memorability. Songs based on the more difficult subtopics in Chemistry were composed, encompassing many equations and facts to be remembered. This technique of song composition can be used in any subject and any tune can be used. This technique can be utilized for any class size, from tutorials to lecture halls. It was found in this study that students understood and retained key information better. In addition, songs added variety to classroom learning experiences, lowered students’ stress levels, increased enjoyment and engaged students more effectively by catering for students with different learning styles.